2004
DOI: 10.1097/00002371-200407000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Plasmacytoma Cells as a Tumor Vaccine

Abstract: Exosomes are membrane-bound vesicles derived from multivesicular bodies that are externalized by cells through fusion with the plasma membrane. Exosomes have been implicated in cell-to-cell signaling, and those derived from immunologic cells may be involved in both direct and cross-presentation of antigens to T cells. The research presented here evaluated their efficacy as a prophylactic cancer vaccine in a mouse plasmacytoma model. Plasmacytoma cells were shown to release exosomes in vitro, and vaccination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Intracellular processing, which probably involves exosome-adhesion molecules (Clayton et al, 2004) that bind to the dendritic-cell surface before endocytosis and processing (Morelli et al, 2004), is certainly compatible with earlier studies documenting exosomes as antigen-deliveryvehicles to dendritic cells (Altieri et al, 2004;Andre et al, 2002;Wolfers et al, 2001). The relative potency of stressderived exosomes in such cross-presentation mechanisms is the subject of ongoing studies in our laboratory.…”
Section: Discussionsupporting
confidence: 76%
“…Intracellular processing, which probably involves exosome-adhesion molecules (Clayton et al, 2004) that bind to the dendritic-cell surface before endocytosis and processing (Morelli et al, 2004), is certainly compatible with earlier studies documenting exosomes as antigen-deliveryvehicles to dendritic cells (Altieri et al, 2004;Andre et al, 2002;Wolfers et al, 2001). The relative potency of stressderived exosomes in such cross-presentation mechanisms is the subject of ongoing studies in our laboratory.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have shown activation of immune responses by tumor exosomes, as prophylactic agents (40) or as therapeutic vaccines in murine cancer models (23) and in humans (11,41), usually by loading them onto enriched dendritic cell populations. By binding and endocytosing exosomes, dendritic cells may crosspresent exosome-delivered antigens to T cells and stimulate antitumor immunity (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…HSP70-80, Her2/Neu, Mart1, TRP and gp100 in melanoma, P1A (intracisternal A particle protein) and HSP70 in plasmacytoma cells. [79][80][81] However, these antitumor immune responses induced by TEXs are relatively weak and prone to induce tolerance. Therefore, these strategies are limited to in vitro observations and mouse model studies.…”
Section: Modified Tumor Cell-derived Exosomes (Texs)mentioning
confidence: 99%